Biblioscope and the Variety of Disability Media: The Construction and Institutionalisation of a Swedish Reading Device for People with Physical Impairments, 1954–1966 - Erik Florin Persson (Tijdschrift voor Mediageschiedenis)
In the mid-1950s, the Gothenburg-based photographer Andrej Gavrjusjov constructed a microfilm reading device called Biblioscope, intended for hospital patients with physical impairments. Throughout the following years, reading devices and microfilmed books were distributed to hospital libraries across Sweden, but in the mid-1960s, the Biblioscope was taken out of distribution. By analysing this now largely forgotten technology, the article makes several contributions to the field of disability media studies. With a focus on material and economic factors, and intermedial relations, the article analyses the construction and institutionalisation of the Biblioscope. Although the Biblioscope was mainly aimed at hospital patients with physical impairments, the article highlights speculations about its future potential for a wider set of users, anticipating today’s reading of digital books on portable screens. In conclusion, the analysis shows how media technologies, which today seem self-evident, often have forerunners that were developed for individuals with disabilities.